An uncommon case of apical dentoalveolar abscess of sinusal origin - Brito, Lívia Natália Sales; Santos, Hellen Bandeira de Pontes; Menezes, Nicássio Silva; Pereira, Marcos Alexandre da Franca; Freitas, Roseana de Almeida; Godoy, Gustavo Pina (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Introduction: Apical dentoalveolar abscesses associated with sinusitis are very uncommon and may expose patients to unfavorable outcomes. Case-report: A 25-year-old female patient sought medical care due to severe, recurrent, long-term frontal facial pain and symptom relief through analgesics. A tomographic examination of the skull did not identify any pathological cerebral alterations. It did, however, evidence diffuse and irregular mucous thickening of all nasal cavities. The patient was referred to an otorhinolaryngologist, who diagnosed the condition as bilateral chronic inflammatory rhinosinusopathy. A rhinoscopy was performed and antibiotic associated with corticoid was prescribed. After the procedure, sinus infection diffusion to the dental tissues was observed, and the patient required emergency dental care due to diffuse facial cellulitis and swelling associated to tooth 26. Due to the absence of clinical signs indicative of carious infection, the condition was diagnosed as an uncommon case of acute dentoalveolar abscess of sinusal origin. After endodontic access for initial drainage, chemical-mechanical preparation of the root canals was performed, in two sessions. After 30 days, a tomography of the sinuses was performed, and results indicated a significant improvement of the infectious process. Due to the rarity of the case presented herein, it is of significant importance to understand the clinical, radiographic and protocol aspects of the case, in order to attend similar cases, as well as the joint action of the dental surgeon and the otorhinolaryngologist for rhinogenic and odontogenic infection management.